2010
DOI: 10.1038/nmeth.1432
|View full text |Cite|
|
Sign up to set email alerts
|

Exploring the sequence determinants of amyloid structure using position-specific scoring matrices

Abstract: Protein aggregation results in beta-sheet-like assemblies that adopt either a variety of amorphous morphologies or ordered amyloid-like structures. These differences in structure also reflect biological differences; amyloid and amorphous beta-sheet aggregates have different chaperone affinities, accumulate in different cellular locations and are degraded by different mechanisms. Further, amyloid function depends entirely on a high intrinsic degree of order. Here we experimentally explored the sequence space of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
651
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 600 publications
(677 citation statements)
references
References 40 publications
21
651
0
5
Order By: Relevance
“…The aggregation of proteins into amorphous aggregates results in a loss of function (Reumers et al, 2009;Rousseau et al, 2006a) and consequently has not been observed as a way to generate functional materials. Many years of intense in vitro study of peptide and protein aggregation have shown that almost all proteins can form amorphous aggregates when induced at high concentration, but under a set of native-like conditions only some are able to form highly ordered brich amyloid fibrils (Maurer-Stroh et al, 2010).…”
Section: Protein Misfolding and Aggregationmentioning
confidence: 99%
“…The aggregation of proteins into amorphous aggregates results in a loss of function (Reumers et al, 2009;Rousseau et al, 2006a) and consequently has not been observed as a way to generate functional materials. Many years of intense in vitro study of peptide and protein aggregation have shown that almost all proteins can form amorphous aggregates when induced at high concentration, but under a set of native-like conditions only some are able to form highly ordered brich amyloid fibrils (Maurer-Stroh et al, 2010).…”
Section: Protein Misfolding and Aggregationmentioning
confidence: 99%
“…Intrinsic disorder was estimated using the IUPred (Dosztányi 2005), RONN (Yang 2005) and VSL2B (Obradovic 2005) algorithms, transmembrane helix forming propensity using DAS-TMfilter (Cserző 2004), TMHMM (Krogh 2001) and PHOBIUS (Käll 2004) and aggregation propensity using FoldAmyloid (Garbuzynskiy 2010) and the TANGO/WALTZ (Fernandez-Escamilla 2004;Maurer-Stroh 2010) algorithms. None of these predictors use evolutionary information during data processing, thus we expect that they can be used for de novo sequences in an unbiased way.…”
Section: Methodsmentioning
confidence: 99%
“…This has been exemplified in a study which showed that -lactoglobulin A modified with Nethylmaleimide largely resisted aggregation induced by heating . Extensive knowledge of the molecular factors driving the aggregation process of proteins has lead to the development of a number of algorithms able to predict protein aggregation with high fidelity DuBay et al, 2004;Fernandez-Escamilla et al, 2004;Maurer-Stroh et al, 2010).…”
Section: Aggregation and Gelationmentioning
confidence: 99%